PENGARUH RENDAMAN AIR LAUT, AIR HUJAN, DAN AIR PAYAU TERHADAP KUAT TEKAN BETON - Arjuna, Arjuna; Jasman, Jasman; Muis B, Abd. (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
Water is an essential fundamental component in the manufacture of building materials (concrete) and reinforced concrete (steel) constructions. In construction, water acts as a component, transforming the hydraulic adhesive into a paste that will ultimately harden. Apart from that, the water in the concrete mix activates the chemical process of cement as an adhesive and lubricates the aggregate, making it easier to work with. The purpose of this study is to assess the influence of immersion water on concrete compressive strength in order to calculate the immersion-to-concrete strength ratio. This research method uses experimental research methods by comparing between 3 types of immersion water in concrete, namely AL (sea water), AP (brackish water), and AH (rainwater). The results of the research on the compressive strength of AL of 19.24 MPa, AP of 20.90 MPa, and AH of 24.33 MPa. AL experienced a decrease in compressive strength of 3.36 MPa and AP of 5.09 MPa against AH which has the highest strong value among the 3 bath variations and even higher than the compressive strength of the plan of 20 MPa. From the clarification over, it can be concluded that the submersion of brackish water, and water comes to the compressive quality of the arrange, whereas the inundation of seawater does not meet.